PENGARUH TINGKAT LIKUIDITAS DAN SOLVABILITAS TERHADAP KINERJA PERUSAHAAN BARANG KONSUMSI DI BURSA EFEK INDONESIA - Cut Nora Ayunda; Ainun Zairinah (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2016)
This study, entitled "The Influence of Liquidity and Solvency Performance Against Consumer Goods Company in Bursa Efek Indonesia". The purpose of the study was to examine the effect of the level of liquidity and solvency levels on the performance of consumer goods companies listed in Indonesia Stock Exchange. The data used in this research is secondary data, time series data (time series) 2009-2013. The source data comes from consumer goods company 6 food and beverage industry sectors listed on the Indonesia Stock Exchange. Data processing was performed with SPSS. The results showed that: (1) The level of liquidity and solvency levels have a relationship (correlation) with the performance of companies that are consumer goods sector, the food and beverage industry are listed on the Indonesia Stock Exchange; (2) The level of liquidity and solvency levels have to explain the performance of the company influence consumer goods sector, the food and beverage industry are listed on the Indonesia Stock Exchange amounted to 15.6 %% while the remaining 84.4% is influenced by other variables outside the model of this research; (3) In partial liquidity level does not significantly influence the company's performance consumer goods sector, the food and beverage industry are listed on the Indonesia Stock Exchange; (4) The level of solvency does not significantly influence the company's performance consumer goods sector, the food and beverage industry are listed on the Indonesia Stock Exchange; and (5) Testing simultaneously, the level of liquidity and solvency levels have a significant effect on the performance of consumer goods companies food and beverage industry sectors listed on the Indonesia Stock Exchange.